'Flying high?'—Jump from a height in a 'Spice' high?: A case report on the synthetic cannabinoid 5F‐MDMB‐P7AICA. Issue 3 (22nd November 2022) - Walle, Nadja; Doerr, Adrian A.; Schmidt, Peter H.; Schaefer, Nadine
Abstract: Regarding the high potency of synthetic cannabinoids (SC), many intoxications and fatal cases are reported in literature. Here, we report on a fatality with 5F‐MDMB‐P7AICA contributing to the occurrence of death. A 31‐year‐old man died 10 h after he fell from the rooftop of a house. Police investigations revealed that he had consumed a 'legal high' herbal blend some hours earlier. An initial toxicological screening for new psychoactive substances (NPS) was negative. One year after, the analysis of confiscated drug samples revealed the SC 5F‐MDMB‐P7AICA being unknown at the time of the first investigations. Hence, post‐mortem specimens were retrospectively analysed for 5F‐MDMB‐P7AICA and its dimethylbutanoic acid (DBA) metabolite. Lung, liver, kidney and bile fluid (BF) of the decedent were analysed following solid‐phase extraction and standard addition, heart blood (HB) and peripheral blood (PB) by fully validated liquid–liquid extraction and protein precipitation methods. Additionally, hair specimens were analysed to examine a possible chronic consumption of the SC. All specimens were analysed by liquid–chromatography tandem mass spectrometry. 5F‐MDMB‐P7AICA was detected in HB (0.69 ng/ml), PB (1.2 ng/ml) and hair. DBA was found in HB (46 ng/ml) and PB (5.7 ng/ml) and could additionally be identified in liver and kidney (approximately 4–5 ng/g), lung (approximately 12 ng/g) and BF (approximately 60 ng/g). Compared with the parent compound, much higher concentrations of DBA were quantified. This case shows that drugs found at the scene can provide helpful initial information for further toxicological screenings in biological samples, especially when there is evidence of NPS consumption.